Peningkatan Hasil Belajar Biologi pada Materi Keanekaragaman Hayati dengan Model Pembelajaran Langsung (Direct Instruction) pada Siswa Kelas X1 SMA (Universitas PGRI Sumatera Barat, 2017)
This study aims to improve the teaching and learning activities and learning outcomes of student second years senior high school at class X1 SMA with direct instruction models. This research is classroom action research (CAR) with a descriptive method that used two cycles, each cycle consisting of four stages as follows: planning phase, implementation phase, observation phase and reflection phase. Subjects researchers are students of second years senior high school at class X1 SMA. Data collection techniques used were observation and tests. The instrument of research consisted of observation sheets and test sheets. Results of the analysis of observation data by learning cycle 1 obtained an average score of 46,6 (good) cycle 2 increased to 80 (excellent). In cycle 1 the average value is 66.4 with of the percentage grade 21,42 % (minimum criteria of mastery learning is not reached), in cycle 2 increased with the average value of 81,07 and percentage grade is 89,28 % (minimum criteria of mastery learning is achieved). Can be concluded that the direct instructional model can improve the students' learning activities and learning outcomes of biology courses of students in the second years senior high school at class X1 SMA.